Myelin Repair: From Animal Models to Humans - Cayre, Myriam; Falque, Marie; Mercier, Océane; Magalon, Karine; Durbec, Pascale (Frontiers in Cellular Neuroscience, 2021)
Brain repair is commonly considered as non-existent; yet, myelin regeneration is a clear counter example. Following injury or in multiple sclerosis, spontaneous remyelination is observed, with high variability among patients and lesions. Since myelin repair is required for optimal functional recovery, deep knowledge of cells and mechanisms involved in this process is essential to develop new therapeutic strategies. In this review, we will present how animal models and modern methods of cell tracing and imaging have contributed to identify which cell types participate to myelin regeneration. Beside oligodendrocyte progenitor cells that were identified in the nineties as the main source of remyelinating cells in the central nervous system (CNS), other cell populations including subventricular zone-derived neural progenitors, Schwann cells and even spared mature oligodendrocytes have more recently emerged as potential contributors to CNS remyelination. We will also point to identified conditions that limit endogenous repair such as aging, chronic inflammation, and extracellular matrix proteins and the implication of astrocytes and microglia in these processes. Finally we will present some discrepancies between observations made in human and rodents, and discuss how findings from experimental models relate to myelin repair in humans. These considerations are particularly important for therapeutic perspectives.